(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
This paper aims to propose that Heidegger's Being and Time, in particular Heidegger's conceptions of Sorge (care) and Fürsorge (concern for others), and the ethics of care can be complementary. As I argue, insofar as Heidegger's fundamental ontology can be shown to deepen theoretical and ontological grounds for the ethics of care, the normativity of care, developed by care ethicists, that is founded upon the ontology of relationships is related to Heidegger's conception of authentic care, solicitude (Fürsorge). The complementary contributions of Heidegger's fundamental ontology and the ethics of care, in my argument, are essential to the success of each tradition of care. In addition, the complementary view is understood as co-disclosures of Mitsein between the ontological structure of Mitsein and the caring practices within the ontic home of everydayness. Insofar as the pursuit of one's well-being could include the well-being of others, we are heading for a shared political solidarity where Mitsein will always be an issue for the caring citizens.